Implementasi Konsep Pesantren Di Era 5.0 Dalam Menghadapi Tantangan Pengembangan Sumber Daya Manusia Yang Berkualitas - Suriyati, Suriyati; Kahar, Kahar; Jaya Nur, Makmur; Annisa Sudarsifa, Nurul; Zulfikar, Zulfikar (Jurnal Al-Ilmi Jurnal Riset Pendidikan Islam, 2025)
Society 5.0 is a society that can solve various social challenges and problems by utilizing various innovations that were born in the era of the Industrial Revolution 4.0 such as Internet on Things (internet for everything), Artificial Intelligence (artificial intelligence), Big Data (large amounts of data), and robots to improve the quality of human life. The aim of this research is to find out how the Islamic boarding school concept in the 5.0 era faces challenges in developing quality human resources. The research method used is qualitative with library research studies, namely by taking data sourced from books, journals, the internet, and so on. Data analysis is used, namely the context analysis method, which is an effort to collect and organize data, then it is also attempted using analysis and interpretation or interpretation of these data. The results of this research show that implementing the concept in the 5.0 era can increase quality human resources because in this context, Islamic boarding schools have a strategic role in preparing the young generation who not only have intellectual skills, but also strong moral and spiritual strength.